A review of the features and applications of ZIF-8 and its derivatives for separating CO2 and isomers of C3- and C4- hydrocarbons - Manel Bergaoui (17191585) (2021)
Metal organic framework (MOF) membranes have gained more attentions due to their abilities in various applications in gas and liquid separations. The majority of works are related to Zeolite imidazolate frameworks-8 (ZIF-8). This is often attributed to its high stability, easy synthesis, and good gas separation. They have gained a significant interest of scientists and have the aptitude to be utilized in other gas separations and applications. Indeed, the investigation of the literatures revealed that ZIF-8 and its derivatives have a substantial attention due to of its good properties as its large specific surface area, “gate opening” mechanism, etc …, which makes them special in adsorption/membrane separations and other associated aspects. The applications of ZIF-8 based materials for carbon dioxide (CO2) gas adsorption and the C3- and C4- isomers’ (propane, propylene, n-butane and isobutane) gas separation also are discussed. Statistical physics approach was applied throughout this review as a perfect tool to discuss and understand properties of ZIF-8, especially the “gate opening pressure”. Subsequently, this review points to present highlights and applications of ZIF-8 and its derivatives for the purpose of carbon dioxide and hydrocarbon separations. Additionally, this study considers recent advancements of ZIF-8 synthesis and prospects for its use in gas separation. This study can help to better understand effective features of a sorbent and methods for gas separation process. As theoretical discussions are referred to as a crucial issue, this is the first study on Zeolitic Imidazolate Framework (ZIF) membrane application, which provides the use of statistical physics theoretical approach and considers the effect of nanogate opening pressures. Other Information Published in: Journal of Natural Gas Science and Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jngse.2021.104289